Treosulfan-Based Conditioning Regimen for Second Allograft in Patients with Myelofibrosis - (:unkn) unknown (My University, 2020)
Relapse after allogeneic hematopoietic stem cell transplantation (AHSCT) in myelofibrosis (MF) patients remains as a significant issue despite advances in transplantation procedures and significant prolongation in survival. Second AHSCT is a potential treatment option but associated with high treatment-related mortality and novel less toxic conditioning regimens are needed. In 33 MF patients with relapse after AHSCT and failure to donor lymphocyte infusion (DLI) we investigated treosulfan (36–42 g/m2) in combination with fludarabine and anti-thymocyte globulin (ATG) as conditioning regimen for a second AHSCT with matched related (n = 2), unrelated (n = 23), or mismatched unrelated (n = 8) donors. All patients achieved leukocyte engraftment after a median of 11 days, and 56 ± 13% experienced acute GVHD grade II–IV at day 100. The therapy-related mortality at day 100 and at 3 years was 16% and 31%, respectively. The cumulative incidence of relapse at 5 years was 16%, resulting in a 5-year disease-free and overall survival of 45% and 47%, respectively. Treosulfan-based conditioning for second allograft in relapsed MF patients resulted in about 50% of the patients in long-term freedom from disease.